EPISTEMOLOGI ‘ILM LADUNNI PERSPEKTIF ABU HAMID AL-GHAZALI - Rohman, Ahmad Yani Fathur (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
The purpose of this research is to explain the epistemology of Laduni Science in al-Ghazali's perspective. There are three epistemologies in Islamic science itself, including bayani, burhani, and 'irfani. Al-Ghazali's style of thought is bayani and 'irfani. Laduni science is the hallmark of al-Ghazali's scientific thought, especially from the 'irfani aspect which is reinforced through the Al-Quran and Hadith. This research uses the library research method. The result of this research is that Laduni Science according to al-Ghazali is knowledge that is directly given by Allah Swt., without intermediaries. Laduni knowledge is only given to his servants who have devotion to Allah Swt. in totality. To get Laduni Science according to al-Ghazali, first, try to achieve all knowledge and take the most rations from the most knowledge. Second, al-riyadah al-sadiqah and al-muraqabah al-sahihah, and still fear Allah Swt. truly. Third, tafakkur when the soul has learnt some knowledge. Fourth, purifying the rabb?niyyah heart which is adorned with dhikrullah.